Effectiveness of Targeted Advisory Interventions in Enhancing Welfare on Dairy Farms - Susy Creatini; Cristina Roncoroni; Federica Salari; Iolanda Altomonte; Giovanni Brajon; Mina Martini (Animals)
Animal welfare assessments have raised farmers’ awareness of their management practices, contributing to measurable improvements. However, these protocols often highlight critical points without providing clear guidance on the prioritization of corrective actions. To address this gap, qualified advisory support may play a pivotal role in translating assessments into effective and sustainable interventions. This study evaluates the impact of direct and continuous expert support on improving animal welfare in dairy farms. Data were collected from 21 dairy farms in southeastern Tuscany (Italy) using the Classyfarm (CReNBA) protocol. Each farm underwent two assessments at a three-month interval (T0 and T1), during which tailored support was provided to address specific criticalities. At T0, over 60% of the farms obtained only marginally acceptable welfare scores (mean 67.48 ± 4.75), with major deficiencies in farm management practices, particularly regarding hygiene and space management. At T1, all farms showed substantial improvements, with an average increase of 22% in total welfare scores (mean 82.05 ± 5.71) and a mean of nine improved parameters per farm. These findings underscore the effectiveness of structured, continuous consultancy in not only resolving critical issues but also in fostering more informed, proactive, and sustainable farm management. The direct involvement of experts appears to be a key driver in enhancing both animal welfare and operational outcomes in dairy farming.